DAMPAK INKLUSI DAN DIGITALISASI PERPAJAKAN TERHADAP MINAT GENERASI MUDA TAAT PAJAK - Wirayana, I Made Adhi; Utthavi, Wayan Hesadijaya; Sumiari, Kadek Nita (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The tax collection system that applies in Indonesia is a self-assessment system. This system is very dependent on the awareness and active role of the community in fulfilling existing tax obligations. This study aims to find out whether tax inclusion has an effect on the interest of the tax-abiding young generation? and does the digitalization of taxation affect the interest of the young tax-abiding generation? This research was conducted at the Bali State Polytechnic. The number of samples is 54 young people. The sampling technique is the saturated sample method. The analysis technique used, Validity and Reliability Test and PLS SEM analysis. The results of the study show that tax inclusion has a positive effect on the interest of the tax-abiding young generation and tax digitalization also has a positive effect on the interest of the tax-abiding young generation.